STRATEGI PENGEMBANGAN BISNIS HIVE STUDIO AGENCY DENGAN PENDEKATAN BUSINESS MODEL CANVAS - Raihan Yuanda; Rafi Hilal Zahir; Ihsan Lana Valenza; Wien Kuntari (CV. Denasya Smart Publisher, 2024)
The creative industry has become one of the most strategic sectors in global economic development, including in Indonesia. Hive Studio Agency, a digital creative startup, offers graphic design, website development, and digital solutions such as domain and hosting. Despite significant growth potential, the company faces challenges due to intense competition and a lack of an adaptive business model. This study analyzes the company's strategy using the Business Model Canvas (BMC) approach to identify key elements for improvement. Findings indicate that Hive Studio Agency can enhance competitiveness and sustainability by refining value propositions, optimizing customer relationships, and strengthening key partnerships. The research contributes to developing actionable strategies for Hive Studio Agency and provides insights for other startups in navigating the dynamic digital creative industry.